The structure and formation of giant Marimo (Aegagropila linnaei) in Lake Akan, Japan - Keisuke Nakayama (Nature Portfolio, 2021)
Abstract Aegagropila linnaei is a freshwater green alga, which at one time was distributed widely in the northern hemisphere. The aggregate often forms beautiful spherical shapes known as “lake balls” or “Marimo”. The population of Marimo has been rapidly decreasing worldwide, and today the large Marimo, with a diameter of more than 12 cm, exit only in Lake Akan in Japan. However, how Marimo grow and maintain their unique spherical shape in natural habitats remains unsolved. Here we show that Marimo are “polished” into spheres by the rotation induced by wind waves. Such a process enhances the water exchange between the interior and exterior of the Marimo, thereby recycling nutrients for growth. Our results provide an intriguing model of a physical environment interacting with biological processes in a self-sustaining ecosystem. We also demonstrate that Marimo have a spherical annual ring structure, and their growth rate is associated with ice cover. The balance between the ecology of Marimo and the water environment in Lake Akan is highly vulnerable and at risk of irreversible degradation. We must endeavor to rescue Marimo from the fate of a "canary in the coal mine" of global climate change.